The Influence of Gas Type and Flow Rate on Plasma Jet Length and Gas Temperature - Ahmed, Mohammed H.; Humud, Hammad R. (Iraqi Journal of Physics, 2025)
This study developed a plasma jet system using a power source that provides a high voltage of 10 kV and a total output power of 30 W. The system operates with three gases: air, nitrogen, and argon. The setup features a plasma torch placed within a steel tube with an internal diameter of 1.4 mm and a length of 5 cm. The research focused on the significance of gas temperature and plasma jet length, investigating how the type of gas and its flow rate influence these parameters. Electrical diagnostics were performed on the system using a high-voltage probe and a calibrated current probe with resistive measurements. The working gas temperature was found to be close to the ambient temperature across various flow rates. Nitrogen exhibited the highest temperature, measuring 22.8°C at a gas flow rate of 1 L/min and decreasing slightly to 22.6°C at 5 L/min. Air showed a relatively stable temperature, with 22.4°C at 1L/min and 22.3°C at 5 L/min. Argon had the lowest temperature, with 22.6°C at 1 L/min, decreasing to 21.8°C at 5 L/min. The plasma jet length varied by gas type, with argon producing the longest jet 5.6 cm, followed by air 4.1 cm and nitrogen 2.6 cm at a gas flow rate of 5 L/min. The jet length increased with higher gas flow rates for all three gases. The system operates with air, nitrogen, and argon, maintaining near-ambient temperatures, making it suitable for biological and medical applications like seed germination and wound sterilization.